Rol de las subunidades GluN2A y GluN2B, del receptor NMDA en la formación de memorias - Ubilla Gallegos, Carmen (2018)
The N-methyl D-Aspartate glutamate receptors (RNMDA) take part in processes of neuronal\nand synaptic plasticity and are believe to be involved in memory processing. They are some\nof the most important types of receptors that mediate the special transmission by glutamate,\nthough not the current neurotransmission, which is mediated by receptors such as RAMPA.\nThe RNMDA are expressed in the whole nervous central system, especially in the\nhippocampus, cerebral structure that takes part in the formation of special memories, giving\nplace to long term memories.\nIn this work it has been studied the role of the regulatory subunits (GluN2A and GluN2B) of\nthe RNMDA in the establishment of new memories, by reducing their expression. We used\nviral vectors that express anti-sense sequences against the ARNms of the GluN2A and\nGluN2B subunits. These vectors were inoculated into the hippocampus using estereotaxic\nsurgery in Wistar rats, and their effects in learning and memory were evaluated using Open\nField (OF) and Inhibitory Avoidance (IA) tests. The expression of the transgenes was\nevaluated by ?Western blot" and "Polimerase Chain Reaction?. We observed a significant\ndecrease of the expression of GluN2A, in the group of rates inoculated with vectors that\nexpressed sequences anti-sense against this subunit. Nevertheless, this decrease did not\naffected the performance of the animals in the behavioral tests mentioned before, showing\nworking and long term memory.